A Review of Treatments for Young Black Males Experiencing Depression. (March 2018) - Lindsey, Michael A.; Banks, Andrae; Cota, Catherine F.; Lawrence Scott, Marquisha; Joe, Sean
The objective was to qualitatively examine the treatment effects of depression interventions on young, Black males (YBM) across treatment providers and settings via a review. Randomized controlled trials (RCTs) seeking to ameliorate depressive symptomology in Black males ages 12–29 were eligible for inclusion. After review of 627 abstracts and 212 full-text articles, 12 studies were selected. These RCTs were organized into five categories based on the intervention method. We isolated only one study that targeted YBM exclusively. Additionally, only two treatment effect sizes for YBM were available from the data. While remaining RCTs did involve Black youth, disaggregated data based on race and gender were not reported. Overall, the lack of research specific to YBM prevented any strong conclusions about the treatment effects on depression for this population. Small sample size along with poor representation of YBM were trends in the selected studies that also posed an issue. Therefore, our review produced qualitative findings but failed to isolate any true effect size for YBM being treated for depression. Until more conclusive evidence exists, alternative strategies may need to be employed in order to find appropriate interventions for depressed YBM seeking mental health treatment.